Advances in the imbalance of the immune microenvironment in the chronically photodamaged skin - Xinling CHEN; Yu SUN; Yuhan JIANG; Yue ZHENG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
In recent years, the mechanisms of repeated ultraviolet light (UV) radiation-induced spatial and temporal changes in the immune microenvironment and the imbalance are the hot research topic in the fields of skin, immunity, tumor and aging. Chronic UV radiation (UVR) can induce cellular phenotypic and functional changes in the skin microenvironment, and directly and indirectly alter the skin immune microenvironment. UVR induces immunosuppression, including activation of regulatory T cells and alterations in the number and function of antigen-presenting cells. The interactions among B cells, T cells, Langerhans cells and mast cells play an important role in UVR-induced immunosuppression. In addition, the effects of UVR on T cell co-inhibitory and co-stimulatory signals have been increasingly appreciated. In this paper, we review the recent progress in the imbalance of the immune microenvironment in the chronically photodamaged skin.